The Incidence and Risk Factor Analysis of Drug Induced Liver Injury (Dili) in a Surabaya Hospital - Arrang, Sherly Tandi; Widyati, Widyati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2018)
The research has been conducted on the incident and analysis of risk factors drug liver injury (DILI) in a Surabaya Hospital. The aim of this study was to determine the incident of DILI, know which drugs cause DILI, and see the association of risk factors to DILI. The research method was descriptive and analytical observational (prospective cohort). Danan-Benichou scale is a tool used to ascertain drugs that cause DILI. Based on data collected for 3 months, the population was 1202 patients. Samples fulfilling the inclusion and exclusion criteria were 310 patients, the risk drug group of DILI were 285 patients (11 DILI, 274 Non-DILI), and the non-risk drug group 25 patients (11 DILI, 14 Non-DILI). The incident of DILI was 3.55%. Drugs that cause DILI are ranitidine (4 cases), omeprazole (1 case), rifampicin (2 cases), meropenem (1 case), ciprofloxacin (1 case), methotrexate (1 case), and dexamethasone (1 case). Characteristic of patients with DILI (11 patients) are average age of 59.27 Â± 15.54 years (23-73 years), belonging to high risk group (54.55%), male gender (81,82%), have moderate comorbid disease (54.55%), and are not comsumsing alcohol (100%). This research use logistic regression analysis through SPSS 17.0 program to see the relation of risk factor to DILI incident. The p results were obtained from sex (0,156), age (0,534), and comorbid isease (0,213)> Î± (0,05) which means gender, age, and comorbid disease do not significantly affect the incident of DILI.